English as a Foreing Language Learners’ Perception of Internet Media on English Speaking Skill - Rofi’uddarozat Rofi’uddarozat; Tarmidzi Tibyan Purnama; Dedi Sulaeman (Jurnal Perspektif, 2025)
English is a dominant global language, with internet media playing a crucial role in language learning. This study examines EFL learners’ perceptions of internet media’s impact on speaking skills, focusing on vocabulary, pronunciation, and fluency. Using a descriptive qualitative approach, data were collected through interviews with five EFL learners from diverse backgrounds. The results indicate that internet media, particularly YouTube, social media, and online games, enhance language acquisition through exposure to authentic content. However, barriers such as the lack of conversation partners and low confidence hinder speaking practice. While internet media facilitates passive learning, interactiveengagement remains essential for fluency. This study recommends integrating video-based learning and interactive language platforms to enhance speaking skills effectively.